The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s00167-007-0368-y
|View full text |Cite
|
Sign up to set email alerts
|

Double bundle or single bundle plus extraarticular tenodesis in ACL reconstruction?

Abstract: Anatomic reconstructions of anterior cruciate ligament (ACL) with double bundle gracilis and semitendonosus tendons graft, reproducing AM and PL bundles, have been introduced to offer a better biomechanical outcome, especially during rotatory loads. On the other hand, many methods of tenodesing the lateral aspect of the tibia to the femur to reduce internal rotation (IR) of the tibia and minimize anterior translation of the tibia relative to the femur as a backup for intra-articular reconstruction, have been a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(110 citation statements)
references
References 34 publications
7
101
1
1
Order By: Relevance
“…But as there is a variety of possible tools for measuring the rotational stability in the lab, the manual pivot shift test still remains the only validated parameter in the daily clinical routine. Even if there is an attempt of an objective quantitative measurement by several technical devices [17][18][19][20], objective quantitative assessment of the pivot shift phenomenon is currently lacking and the evaluation greatly depends on the examiner's subjective experience and impression [21,22]. Therefore, accurate assessment of the pivot shift is essential to obtain an exact clinical assessment of ACL-deficient or reconstructed knee.…”
Section: Discussionmentioning
confidence: 99%
“…But as there is a variety of possible tools for measuring the rotational stability in the lab, the manual pivot shift test still remains the only validated parameter in the daily clinical routine. Even if there is an attempt of an objective quantitative measurement by several technical devices [17][18][19][20], objective quantitative assessment of the pivot shift phenomenon is currently lacking and the evaluation greatly depends on the examiner's subjective experience and impression [21,22]. Therefore, accurate assessment of the pivot shift is essential to obtain an exact clinical assessment of ACL-deficient or reconstructed knee.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 Recently, it was shown that performing lateral extra-articular tenodesis in association with intra-articular reconstruction of the ACL using a single bundle might be superior to intraarticular ACL reconstruction with a double bundle, from a rotational point of view, which confirms the importance of these extra-articular structures. 28 The rationale of combining intra-and extra-articular procedures in ACL reconstruction is to limit the internal rotation of the reconstructed knee, thus providing more knee stability in the rotational axis and preventing excessive stresses on the ACL graft. Many studies have already investigated the role of such extraarticular procedures.…”
Section: Figmentioning
confidence: 99%
“…We have recognized two reports of the same study; although we combined useful data from both reports, most relevant information was extracted from the full text report [14]. We excluded another study [29] that was not an RCT. The remaining eight studies (Appendix 2; supplemental materials are available with the online version of CORR 1 ) met the inclusion criteria for our systematic review ( Fig.…”
Section: Search Strategy and Criteriamentioning
confidence: 99%